Sensing, feeling, thinking: Relating to nature with the body, heart and mind. Issue 2 (29th November 2021) - Pramova, Emilia; Locatelli, Bruno; Valdivia‐Díaz, Merelyn; Vallet, Améline; Quispe Conde, Yésica; Djoudi, Houria; Colloff, Matthew J.; Bousquet, François; Tassin, Jacques; Munera Roldan, Claudia
Abstract: The cultural ecosystem services (CES) construct has evolved to accommodate multiple worldviews, knowledge systems and conceptualizations of nature and values, including relational and mental health values. Cultural ecosystem services research and practice has mostly focused on cognitive ways of constructing and expressing intangible values of, and relationships with, nature. But our non‐material relationships with nature are not exclusively cognitive: sensory and affective processes are fundamental to how we build, enact and experience these relationships. Building on the core ideas of relational values, embodied experiences and connectedness with nature, we present a simple framework to explore the sensory, affective and cognitive dimensions of human–nature interactions, as well as the settings and activities that frame them. We demonstrate its use in a case study in the Peruvian Andes, where we applied an inductive, exploratory approach to elicit personal imageries and imaginings related to nature, place and recreation. The narratives shared were rich with symbolism and personal sensory experiences, emotions and memories, which the interviewees linked with general assertions about people, place and nature. We discuss the usefulness of such a perspective for CES research, and for human well‐being, environmental justice and landscape management. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Resumen: El concepto de servicios ecosistémicos culturales ha evolucionado para integrar múltiples visiones del mundo, sistemas de conocimiento y conceptualizaciones de la naturaleza y sus valores, incluyendo los valores de relación y de salud mental. La investigación y la práctica de los servicios ecosistémicos culturales se han enfocado principalmente en las formas cognitivas de construir y expresar los valores intangibles de la naturaleza y las relaciones con ella. Pero nuestras relaciones inmateriales con la naturaleza no son exclusivamente cognitivas: los procesos sensoriales y afectivos son fundamentales para la forma en que construimos y vivimos estas relaciones. Inspirándonos en las ideas principales de los valores relacionales, las experiencias físicas y la conexión con la naturaleza, presentamos un marco sencillo para explorar las dimensiones sensoriales, afectivas y cognitivas de las interacciones entre los seres humanos y la naturaleza, así como los entornos y las actividades que las configuran. Demostramos su uso en un estudio de caso en los Andes peruanos, en el que aplicamos un enfoque inductivo y exploratorio para obtener imágenes e inspiraciones personales relacionadas con la naturaleza, el lugar y la recreación. Las narrativas compartidas fueron ricas en simbolismo y experiencias sensoriales personales, emociones y recuerdos, que los entrevistados vincularon con afirmaciones generales sobre la gente, el lugar y la naturaleza. Discutimos la utilidad de esta perspectiva para la investigación de los servicios ecosistémicos culturales, y para el bienestar humano, la justicia ambiental y la gestión del territorio. A free Plain Language Summary can be found within the Supporting Information of this article.